Analiz tekhniki osnovnykh priyemov v vol'noi bor'be - Morozov, A. K. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this study was to reveal the main holds determining the success in free-style wrestling. The results showed that the dynamics of means and standard deviations of the kinematic and dynamic parameters as well as the bioelectric activity of the main muscle groups can serve as the check points for specialists and coaches working with the elite wrestlers as well as with the beginners. The ranked array according the difficulty`s degrees and the sequence study that the most important group of holds in the free-style wrestling.